2014
DOI: 10.1111/iju.12496
|View full text |Cite
|
Sign up to set email alerts
|

Tamsulosin versus tamsulosin plus tadalafil as medical expulsive therapy for lower ureteric stones: A randomized controlled trial

Abstract: Objectives:To compare the efficacy of tamsulosin versus tamsulosin plus tadalafil as medical expulsive therapy for lower ureteric stones. Methods: Between January 2013 and December 2013, 244 patients presenting with distal ureteric stones (size 5-10 mm) were randomized equally to tamsulosin (group A) or tamsulosin plus tadalafil (group B). Therapy was given for a maximum of 4 weeks. Stone expulsion rate, time to stone expulsion, analgesic use, number of hospital visits for pain, follow up, endoscopic treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
53
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 28 publications
(42 reference statements)
10
53
7
Order By: Relevance
“…It is important to note that drugs A and B act on a-1 adrenoceptor, whereas drug C acts through PDE, which are totally separate pathways in modulation of ureteric motility and thus opening the potential of combining these drugs to further aid the ureteric stone expulsion. Such combination as tamsulosin with tadalafil has already been successfully used by Jayant et al, 25 and this further opens up the potential for combining silodosin with tadalafil. 26 Colicky pain in ureteral stone occurs due to an increase in intraureteral pressure above the site of ureteral obstruction.…”
Section: Commentmentioning
confidence: 96%
“…It is important to note that drugs A and B act on a-1 adrenoceptor, whereas drug C acts through PDE, which are totally separate pathways in modulation of ureteric motility and thus opening the potential of combining these drugs to further aid the ureteric stone expulsion. Such combination as tamsulosin with tadalafil has already been successfully used by Jayant et al, 25 and this further opens up the potential for combining silodosin with tadalafil. 26 Colicky pain in ureteral stone occurs due to an increase in intraureteral pressure above the site of ureteral obstruction.…”
Section: Commentmentioning
confidence: 96%
“…In our initial research, we identified seven studies . Two of them were excluded when we went through the full text because they did not measure up the previous inclusion criteria (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Over the past 10 years, the possibility in MET to use phosphodiesterase type 5 inhibitors (PDE5i) has been studied due to their direct influences on ureteral smooth muscle relaxation in animals and human models . Investigators have focused on how can the effective implementation with PED5i in clinical practice, and the results of these studies displayed that tadalafil prescription owns positive benefits …”
Section: Introductionmentioning
confidence: 99%
“…On the basis of theory, many studies have shown that distal ureteral stones can be successfully treated with different PDE5Is. Jayant et al [3] conducted a randomized controlled trial to compare the efficacy of tamsulosin versus tamsulosin plus tadalafil as medical expulsive therapy for lower ureteric stones (5-10 mm) and found the addition of tadalafil with tamsulosin able to facilitate the ureteric stone expulsion. Recently, Shokeir et al [4] found sildenafil…”
Section: Editormentioning
confidence: 99%